Rechargeable Massage Pillow / Nur Syafiqah Mohd Izuddin - Mohd Izuddin, Nur Syafiqah (2020)
The name of our business is AMOIZ ENTERPRISE. Our business type that we generate is partnership which is the partner has limited liability restricted to the percentages of amount capital invested. The profit or loss will incurred by each partner depend on how much amount capital invested by the partners. The relation among business partner is dictated by the agreement. Our business is producing an innovated pillow called Rechargeable Massage Pillow. It is a pillow with a vibration function. It might help in reducing the pain we feel while travelling, doing works or else. This pillow is made of high-density memory foam which is suitable for any pressure put against it and it will return into its original shape when the pressure is removed. It is light and comfortable too. Our products, design and finishes will continue evolve based on consumer trends and demands.